Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12885-023-11158-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of prognostic nomogram for T1-3N0M0 non-small cell lung cancer after curative resection

Weijian Mei,
Wang Yao,
Zhengbo Song
et al.

Abstract: Background Radical resection plus lymph node dissection is a common treatment for patients with T1-3N0M0 non-small cell lung cancer (NSCLC). Few models predicted the survival outcomes of these patients. This study aimed to developed a nomogram for predicting their overall survival (OS). Materials and methods This study involved 3002 patients with T1-3N0M0 NSCLC after curative resection between January 1999 and October 2013. 1525 Patients from Sun Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies have highlighted the prognostic importance of examining lymph nodes in NSCLC patients, 9 , 10 , 21 , 22 recognizing adequate lymphadenectomy as an independent prognostic factor correlated with better outcomes. However, discrepancies in surgical quality among hospitals and surgeons may affect the extent of lymph node examination, potentially limiting its ability to accurately represent the true N stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have highlighted the prognostic importance of examining lymph nodes in NSCLC patients, 9 , 10 , 21 , 22 recognizing adequate lymphadenectomy as an independent prognostic factor correlated with better outcomes. However, discrepancies in surgical quality among hospitals and surgeons may affect the extent of lymph node examination, potentially limiting its ability to accurately represent the true N stages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a connection between the number of examined lymph nodes and patient survival, with a higher count associated with improved prognosis. 9 , 10 It has been suggested that 10 examined lymph nodes represent an adequate cut-off value for dissection, beyond which there is no further improvement in prognosis. 10 However, others propose 16 examined lymph nodes as the threshold for assessing the quality of lymph node examination and postoperative prognostic stratification in NSCLC patients who undergo surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, the prognostic significance of examined lymph nodes is an active area of research. Several studies suggest a correlation between the number of examined lymph nodes and patient survival, with higher counts linked to better outcomes [ 29 , 30 ]. However, the prognostic value of lymph node examination can be influenced by the quality of the surgical procedure [ 31 ].…”
Section: Introductionmentioning
confidence: 99%